Aircraft overrun warning systems capabilities and disadvantages - S. F. Borodkin; A. I. Volynchuk; M. A. Kiselev; Yu. V. Petrov (Научный вестник МГТУ ГА, 2023)
Currently, attention of the aviation community and authorities is being increasingly focused on flight safety in the landing phase. It is accounted for the increased frequency of incidents in the final phase of flight and significant threats associated with the consequences of these events. The statistics of aviation accidents reveals that from 1959 to 2019, 55% of aircraft crashes in the world occurred in the phases of landing and takeoff. The given crashes resulted in 51% of all fatalities on board aircraft. In most cases, causes of these aviation accidents are involved with some kind of human error. Off-design conditions at an aerodrome also have a significant adverse effect on the aviation accident potential and severity. The increasing intensity of flights, airspace congestion, strict ATC-imposed restrictions, the necessity to perform a variety of procedures and general flight crew stress in conjunction with dynamically changing external conditions can disorient a flight crew and lead to a landing with a flight envelope overrange. The search for a solution in terms of preventing aircraft overruns is actively being conducted both by aviation authorities and aircraft manufacturers and operators. Within the framework of this review, the major external and operational factors, affecting the dynamics and the nature of the aircraft roll via the runway, are analyzed, including the context of several accidents that have occurred in recent years. In addition, the article emphasizes the methods to prevent and anticipate aircraft overruns based on the principles of active protection. In particular, the article examines the main operation aspects of onboard avionics systems installed on Boeing and Airbus aircraft and highlights the focus areas of their upgrading. Special attention is paid to the influence of the pilot and the possibility of taking his actions into account to predict an outcome of landing.